IMPLIKATUR PERCAKAPAN TOKOH PENDIDIKAN DALAM MEDIA ELEKTRONIK - Al Qodiri, Aisyah; Harun Joko Prayitno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms and meanings of conversational implicatures used by educational figures in electronic media, particularly on YouTube. The data consist of utterances in podcasts and interviews discussing educational issues and curriculum policies in Indonesia on the KOMPASTV channel and Dr. Indrawan Nugroho. The research employs a descriptive qualitative method with a case study approach. The analysis is based on the theory of conversational implicature proposed by Paul Grice, using the pragmatic matching technique. The findings reveal two types of implicature: general conversational implicature and particular conversational implicature. General implicature is used to convey perspectives on shifts in learning paradigms, holistic evaluation, and character development. Meanwhile, particular implicature appears in policy contexts, such as curriculum changes, criticism of the dominance of academic testing, teacher welfare, and the relationship between formal qualifications and professional competence. These findings indicate that implicature functions as a persuasive and non-confrontational communication strategy in expressing ideas and educational critiques..